Neither / Or is not an Option Daniel Solomon’s Housing and the City: Love vs. Hope is really about both (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
If you found the value of Daniel Solomon’s newest book, Housing and the City: Love vs. Hope, in the direct urban query and analysis you would walk away with an immense amount of careful, academic but, also simply relevant concern about cities and what is possible – with creativity. In Love Vs. Hope, Love is calibrated to what Solomon has referred to as the continuous city; a sustained reinvention of historical pattern. Hope refers to distruptions or breaks with history; for better or worse, leaps that break the continuity of urban form. Solomon does not consider himself so much a scholar as a thinker, a practitioner and a deeply careful listener – to history, to leading figures from history, but more so to the tenor of the city itself. He read environments, seeking the forces that made them or more so what assumptions made them possible. Solomon does not avoid the stated / official narratives but he is unique in and completely apart from many of his peers in where and how he unearths the subtext of cities; the voices that are less overt, the assumptions unstated (we all make) that need to be unearthed to in fact confront.Love vs. Hope reveals this in both detail and concept – the effect, both intellectual and material, is that Solomon leaves the reader unable to resort to major dichotomies of our recent histories – divides that often thwart academic discourse and that also leave cities often in the hands of everyone but architects and planners. Solomon moves from the real politic, to the academic as forged in specific eras, but also to the more personal posture of creative intellects.